2022
DOI: 10.3390/sports10040050
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Sex Difference in Technical Skills among Youth Soccer Players in Norway?

Abstract: Female soccer has recently experienced an impressive increase in the number of players, and an impressive improvement in the quality of elite matches. Still, studies show sex differences in match statistics on passing accuracy and the ability to control the ball in international matches, which is explained by a lower skill of level in female soccer players as compared to male players. Therefore, the aim of this study was to evaluate if female youth soccer players had bridged the gap in technical skills to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Talent identification of soccer players is crucial for professional clubs as it is believed to increase the chances of a successful career as an elite player ( McMorris et al, 2000 ; Perroni et al, 2018 ; Sarmento et al, 2018 ; O’Brien-Smith et al, 2020 ; Sørensen et al, 2022 ). The success of a team sport depends on various performance characteristics that are specific to the sport or transferable, such as physical attributes, technical and tactical skills, and psychological traits ( Williams and Reilly, 2000 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talent identification of soccer players is crucial for professional clubs as it is believed to increase the chances of a successful career as an elite player ( McMorris et al, 2000 ; Perroni et al, 2018 ; Sarmento et al, 2018 ; O’Brien-Smith et al, 2020 ; Sørensen et al, 2022 ). The success of a team sport depends on various performance characteristics that are specific to the sport or transferable, such as physical attributes, technical and tactical skills, and psychological traits ( Williams and Reilly, 2000 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The success of a team sport depends on various performance characteristics that are specific to the sport or transferable, such as physical attributes, technical and tactical skills, and psychological traits ( Williams and Reilly, 2000 ; Leyhr et al, 2021 ; Hermassi et al, 2022 ). Profiling can be a useful tool for identifying talent, assessing strengths and weaknesses, determining player positions, and designing physical fitness programs ( McMorris et al, 2000 ; Perroni et al, 2018 ; Sarmento et al, 2018 ; O’Brien-Smith et al, 2020 ; Sørensen et al, 2022 ). Studies have also found differences in physical, physiological, and anthropometric variables among different age groups, playing positions, and categories ( Buchheit and Mendez-Villanueva, 2014 ; Figueira et al, 2018 ; Silva et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary that future studies conduct more valid, reliable, and multidisciplinary assessment procedures in an effort to more accurately and resourcefully identify and develop talented youth athletes (e.g., [24,25]). Furthermore, several studies included in our Special Issue suggest that future directions should consider longitudinal tracking of interacting factors [26], such as the quantity, quality, and type of practice during sport participation [27], as well as monitoring biological maturation [28,29], physical performance [30,31], technical skills [32], and psychological profiles [33,34]. Evaluating how stakeholders communicate and implement these theoretical findings into applied settings will also be important for future research to ensure they are adequately deployed (e.g., [35][36][37]).…”
Section: Future Directionsmentioning
confidence: 99%
“…The most effective way for players is to simulate in-game situations during training process, which allows to show movement actions maximum rapidity. We should consider that all moves, movements and rest in-game actions as a result must be directed on solving command task (Sørensen et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%